Emission and Function of Volatile Organic Compounds in Response to Abiotic Stress - Spinelli, Francesco; Cellini, Antonio; Marchetti, Livia; Nagesh, Karthik Mudigere; Piovene, Chiara (IntechOpen, 2011)
None